26.6k views
4 votes
W=p(u-z) solve for z

User Lucasz
by
5.1k points

1 Answer

1 vote

Answer:
z = (pu-W)/(p)\\\\

We can write this as z = (pu-W)/p

This is the single fraction with pu-W up top and p in the denominator.

Other answers are possible.

===========================================================

Work Shown:


W=p(u-z)\\\\W=pu-pz\\\\W+pz=pu\\\\pz=pu-W\\\\z=(pu-W)/(p)\\\\

An alternative method could have these steps instead


W=p(u-z)\\\\u-z = (W)/(p)\\\\-z = (W)/(p)-u\\\\z = -(W)/(p)+u\\\\z = -(W)/(p)+(pu)/(p)\\\\z = (-W+pu)/(p)\\\\z = (pu-W)/(p)\\\\

User Omikad
by
4.4k points